Mathematical modelling criminality in Lithuania in a context of the East European countries - Rudzkienė, Vitalija (Lietuvos matematikos rinkinys, 2001)
One of the most sensitive indicators of a moral and social state of society is criminality. The paper examines the criminality trends in Lithuania in a respect of the East European countries.Dynamic series allows to decrease differences in crime registration systems and to distinguish the main trends in the rate of criminality. General tendencies of criminality in Lithuania are the same as in Bulgaria, Hungary or Poland. The analysis of differences between the criminality in Lithuania and the average criminality rates in Bulgaria, Hungary and Poland is fulfilled using linear regression model.